(3GbJUGOjGJ GdWGbI GdfGHVI hGdeJLOOIs - (3eMeO(B, (3eGVjs; (3ceGd(B, (3OjHs ((3GdLRGFQ(B:s (3GdecJH GdLGeYj GdMOjKs, 2017)
(3gPG GdcJGH bSe Gdi eONdjf CSGSjf Vef GdGWGQ GdYGe dGbJUGO GdWGbI hgeG (B: (3GdeONd GdGhd (B: (3jJVef YQV GdGWGQ GdYGe dGSGSjGJ GdGbJUGO GdfaWj Vef GdGWGQ GdYGe dGbJUGO GdWGbI (B: (3GdbGYOI GdfXQjI deGgjI GdHJQhd , GdGMJjGWj , GdYQV hGdWdH GdHJQhdj , GdJMOjGJ GdMGdjI hGdeSJbHdjI dbWGY GdHJQhd GdeONd GdKGfj (B: (3NUU ddMOjK Yf GdShb GdOhdj ddHJQhd (B: (3eGgjI GdShb GdfaWj GdOhdj , GdJMdjd GdGbJUGOj ddShb GdfaWj GdOhdj, JPH CSYGQ GdfaW hJGKjQ Pdc GdGbJUGO GdYGdejs
(3HjHdjhZQGajG U(B.247-281s
Keywords: (3GbJUGOs; (3GdWGbI GdeJLOOIs; (3GdWGbI GdfGVHIs; (3GdfaW GdWGbI GdHJQhdjIs